2016
DOI: 10.1371/journal.pone.0152672
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory Evaluation of the Alere q Point-of-Care System for Early Infant HIV Diagnosis

Abstract: IntroductionEarly infant diagnosis (EID) and prompt linkage to care are critical to minimise the high morbidity and mortality associated with infant HIV infection. Attrition in the “EID cascade” is common; however, point-of-care (POC) EID assays with same-day result could facilitate prompt linkage of HIV-infected infant to treatment. Despite a number of POC EID assays in development, few have been independently evaluated and data on new technologies are urgently needed to inform policy.MethodsWe compared Alere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
56
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 15 publications
3
56
0
Order By: Relevance
“…16 Repeating the POCT on the same sample reduced the error rate to 0.5%. Closer analysis of the POCT errors revealed many modifiable factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Repeating the POCT on the same sample reduced the error rate to 0.5%. Closer analysis of the POCT errors revealed many modifiable factors.…”
Section: Discussionmentioning
confidence: 99%
“…While there is some laboratory evaluation data available, 11–14 field evaluations of POCT platforms for EID, particularly at birth, are required prior to implementation. The Alere Q NAT test (Alere Technologies, Jena, Germany) has been shown to perform at a sensitivity of 98.5% (Jani et al, no neonates) 15 and 96.5% overall (93.3% in 92 neonates, Hsiao et al; 99% in 291 neonates, Kroon et al) 16,17 with specificity >99.5% and there are few published data for Cepheid EID POCT in infants or neonates including the EID consortium which gathers data on neonates and infants. 18 …”
Section: Introductionmentioning
confidence: 99%
“…10,11 Nevertheless, our slightly reduced sensitivity at birth to 93.3% is consistent with similarly reduced sensitivities of other POC platforms in children less than 3 days of age. 15,16 …”
Section: Discussionmentioning
confidence: 99%
“…The Alere Detect test was first investigated for early infant detection (EID) in Mozambique and South Africa (19, 20). In these two studies, heel-stick blood samples were tested by the Alere Detect test and the Roche COBAS® AmpliPrep/COBAS® TaqMan® HIV-1 Qualitative Test (Roche HIV-1 qualitative test).…”
Section: Discussionmentioning
confidence: 99%
“…The Alere q HIV-1/-2 Detect (Alere Detect) test is a rapid point-of-care (POC) nucleic acid test (NAT) providing several advantageous characteristics for HIV diagnosis: 1) the requirement for only 25 microliters plasma or whole blood per test; 2) test completion within one hour; 3) detection and differentiation of HIV-1 Group M/N, HIV-1 Group O and HIV-2 nucleic acid; and 4) the only currently available POC NAT able to detect HIV-2 (18). Two studies have demonstrated the feasibility of the Alere Detect test to diagnose HIV-1 infection for HIV-1-exposed infants in South Africa and Mozambique (19, 20). Here, we evaluated the performance of the Alere Detect test for the detection of HIV-1 and HIV-2 in plasma samples collected from HIV-1, HIV-2 and differentiation of HIV-1 from HIV-2, in dually-seropositive patients.…”
Section: Introductionmentioning
confidence: 99%